Cinética do consumo de oxigênio e da frequência cardíaca, índice BODE e a influência de dois programas de treinamento físico em pacientes com doença pulmonar obstrutiva crônica - Pessoa, Bruna Varanda (Universidade Federal de São Carlos, 2012)
The thesis consisted of three studies described below. The study I, entitled: Oxygen uptake and heart rate on-kinetics in patients with Chronic obstructive pulmonary disease (COPD): comparison between cycle ergometry and elliptical equipment aimed to evaluate and compare the kinetics of both oxygen consumption (VO2) and heart rate (HR) in constant work-rate tests on a cycle ergometer (CCT) and on an elliptical machine (ECT) in COPD patients and healthy individuals. Eighteen male COPD patients between 55 and 78 years old with moderate to very severe obstruction (COPD group) and 18 apparently healthy males (control group: CG) were evaluated; the subjects were paired by age and submitted to the following tests on alternate days: 1) symptom-limited incremental cycle ergometer test (IT); 2) CCT and 3) ECT, both at 70% of the maximum intensity obtained in the IT. Expired gases were collected in all tests, and the kinetics of VO2 and HR were analyzed. The COPD group presented significantly higher tau (τ) and mean response time (MRT) for VO2 on the CCT than the CG (p<0.05); however, there was no significant difference on the ECT. Regarding the different tests, the COPD group had a significantly higher τ and MRT on the CCT than the ECT; on the other hand, no differences between the tests were observed in the CG. We conclude that VO2 kinetics are slowed in COPD; however, this depends on the ergometer used for testing. The faster kinetics found on the ECT for the COPD group may be related to the effects of the body position or to higher recruitment of muscle fibers, as well as to the greater ventilatory and chronotropic stress observed in this test. Following, the study II, entitled: BODE index, body composition, peripheral muscle strength and oxygen uptake and heart rate kinetics on a cycle ergometer and on elliptical equipment in COPD patients: there is relationship between them? aimed to determine if there is a relationship between oxygen consumption (VO2) and heart rate (HR) on-kinetics in constant work-rate exercise test on cycle ergometer (CCT) and on elliptical equipment (ECT) with the BODE index and their isolated variables, muscle mass (MM), lean body mass index (LBMI) and with peripheral muscle strength (PMS) represented by one-repetition maximum strength test (1RM) in patients with COPD. Fourteen men patients with moderate to very severe COPD (COPD group), between 55 and 78 years, were submitted to the following tests on alternate days: 1) six-minute walking test (6MWT); 2) IT; 3) CCT and 4) ECT at 70% of the maximum intensity obtained in CPT; 5) 1RM test and 6) body composition evaluation. Expired gases were collected in CPT, CCT and ECT, and response of the VO2 and HR on-kinetics were analyzed. The BODE index was calculated. The BODE index was calculated. The Pearson correlation coefficient (p<0.05) presented a moderate positive relationship between BODE index and τ and MRT of VO2 and HR (r=0.55 and r=0.63; r=0.66 and r = 0.74, respectively); and negative correlation between τVO2 and MRT-VO2 with FEV1 (r=-0.69; r=-0.68), DW- 6MWT (r=-0,.62; r=-0.65) and DW-6MWT %predict (r=-0.64; r=-0.70). Still, significant negative correlations were observed between the τ-HR and MRT-HR with DW-6MWT (r=- 0,.81; r=-0.82) and DW-6MWT %predict (r=-0.83; r=-0.65). Significant correlations between the TRM and τ of VO2 and of HR with MM, LBMI and PMS; and correlations with oxygen consumption (VO2) and heart rate (HR) on-kinetics in ECT were not observed. In general, our data show that patients with moderate to very severe COPD have slowed VO2 kinetics in the CCT compared the ECT. Furthermore, the VO2 and HR on-kinetics in CCT has a moderate correlation with the classification of COPD severity assessed by the BODE index, FEV1 and DW-6MWT, showing that COPD severity, airflow limitation and exercise capacity are reflected by the slowing of the on-kinetics in COPD patients, but it depends on the ergometer. Finally, the study III, entitled: Effect of aerobic/resisted and interval physical training on oxygen uptake and heart rate on-kinetics in patients with COPD: randomized, controlled trial evaluated and compared the effect of aerobic/resisted physical training (TFAR) and interval physical training program on elliptical equipment (TFI) of high intensity on VO2 and HR onkinetics during CCT and ECT in patients with COPD. Eighteen men patients with moderate to very severe COPD, between 55 and 80 years, randomly divided into two groups: nine of the patients had been engaged in TFAR group, and nine in TFI group, were submitted to the following tests on alternate days: 1) IT; 2) CCT, and 3) ECT both at 70% of the maximum intensity obtained in IT, and one repetition maximum test (1RM), being reevaluated after six weeks physical training. program. The TFAR group consisted of aerobic training by thirty minutes, and three sets of fifteen repetitions of resisted training in lower limbs on leg press. The TFI group realized training program on an elliptical equipment, by thirty minutes at 100% of the maximum intensity obtained in IT, separated by 1-min rest periods. The two training groups completed 6 week (3x/week) of exercise training, until completing a total of eighteen sessions. Expired gases were collected in in all tests, and response of the VO2 and HR on-kinetics were analyzed. No significant difference post-training in the TFAR group both tests (CCT and ECT) were observed; but, the TFI group displayed slower VO2 onkinetics (> τ and > MRT) in the CCT and ECT after training. In relation HR on-kinetics, no significant difference in both groups and both constant workload exercise tests post-training were observed. We conclude that the interval physical training program on elliptical equipament lead to slower VO2 kinetics the onset at high-intensity exercise (CCT and ECT) in patients with COPD. Furthermore, the TFAR program is no sufficient to provoke improvements in VO2 and HR on-kinetics in the CCT and ECT.
Keywords: Doença Pulmonar Obstrutiva Crônica (DPOC); Cinética; Consumo de oxigênio; Frequência cardíaca; Índice BODE; Condicionamento físico.; Tolerância ao exercício; Exercício físico; Mortalidade; Índice de gravidade de doença; COPD; Oxygen uptake; Kinetics; Heart rate; Exercise tolerance; Physical endurance; Physical exercise; Mortality; Severity of illness index.; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL